2012
DOI: 10.2319/082811-552.1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pH levels on mechanical and biological properties of nonlatex and latex elastics

Abstract: Objective: To evaluate the influence of pH levels on interarch elastics with regard to force decay and cytotoxicity. Materials and Methods: One nonlatex (NLAO) group and one latex (LAO) group were tested (n 5 10). Elastics were stretched to 25 mm and were held for 1, 6, 12, and 24 hours in artificial saliva solutions with pH levels of 5.0, 6.0, and 7.5. Force magnitudes were measured at 25 mm of activation. The cytotoxicity assay was performed using cell cultures (L929 mouse fibroblast cell line), which were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…They concluded that pH levels of 5 and 6 in the 24 h investigation were not significant contributors to the force relaxation of interarch elastics in comparison to pH of 7. [89]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They concluded that pH levels of 5 and 6 in the 24 h investigation were not significant contributors to the force relaxation of interarch elastics in comparison to pH of 7. [89]…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, these properties are influenced by several factors related to the material such as loss of elasticity, amount of force decay, and composition of the elastics,[4] and also, the environmental factors such as composition of saliva, intraoral pH and temperature variations, food texture and pigments. [48910] A few studies have evaluated the effect of salivary pH and its changes on the force degradation of latex elastics. [811] Previous studies found no correlation between changes of salivary baseline pH and the force relaxation of elastic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are not considered ideal materials due to the decline in force required for efficient tooth movement 11 . Several studies 6,7,[12][13][14] have been conducted with the purpose of investigating mechanical and environmental factors that contribute to the degradation of force in orthodontic elastics. Santos et al 2 , in a study conducted in 2007, reported that elastomeric chains exposed to piquant foods, humidity and high temperatures presented greater deterioration in force than those exposed to only water, which is in accordance with the findings of Evangelista et al 10 in 2007, who affirmed that factors such as chemical and salivary enzymes, and variations in temperature and pH, would be associated with relaxation and deformation of the polymer.…”
Section: Discussionmentioning
confidence: 99%